CV Amg Farm and Food Garden Banjar Manik Gunung Selanbawak Village Marga District Tabanan Regency - Desak Gede Dwi Arini; Ni Made Sukaryati Karma; Ida Ayu Made Wahyuni; Ni Made Ratna Pratiwi (Fakultas Hukum, Universitas Warmadewa, 2023)
As a higher education institution, Warmadewa University must be ensured to always obey the Tri Dharma of Higher Education in accordance with the predetermined vision and mission. Now every lecturer is encouraged to be able to package community service activities both in groups and individuals who will show concern for the community. Community service activities can be carried out by enlightening by providing legal counseling and consultation, socialization and assistance to the community in various fields of life in the economic field. One of the things that deserves to be observed in the devotion done to CV. AMG Farm And Food Garden Banjar Manik Gunung Selanbawak Village, Marga District, Tabanan Regency, with the existence of a goat livestock business, it must be cultivated to the wider community because it has a fairly high business development potential. The goat livestock business is not only useful for meat to be consumed but goat manure and urine is used for plant organic fertilizer and goat milk is used for cosmetics, and goat skin is used for leather bags. It is hoped that the public will explore knowledge about how to maintain goats properly and correctly in order to get the expected results and profits, good business management and marketing strategies for goat livestock businesses whose manure and urine are used for organic fertilizer for plants such as bananas, durians, pineapples, mangosteen, and kecipir fruit vegetables, using online media and offline media, then collaborating with partners to make agreements in writing with the aim of creating legal certainty for the parties and at the same time the goat livestock business aims to improve the community's economy. The expected output is in the form of publication of journal articles in the Comunity journal of law, print media publications, activity videos, IPR and community service reports in 2022.